PENGGUNAAN METODE ROLE PLAYING DALAM PENGEMBANGAN KEMAMPUAN SOSIAL EMOSIONAL ANAK USIA DINI - Mahmudah, Puput Ayyun (Universitas Islam Darul Ulum, 2023)
From the results of research in this journa regarding the use of role playing methods in developing the social emosional abilities of early childhood. He researcher eants to now about evets that very often occur in early childhood today. Namely the ability which is less developed. It is know that there are several factors, which affects the social development of early dhildhood, such as a lack of activity with the setrrounding environment which causes later children to not wan to be invitee of work together, become introverts, prefer to play alon, like to sort out friendships. This research uses a literature study method ehite data collection. The journal book is in accordance with the theme of the study being researched. The tame is like the word of children, namely role playing with ron playing. Children can activity interact with their friends. Therefore the social emotional development of early childhood ean be feal well.